SOCIAL MEDIA AS A JUST-IN-TIME-MARKETING-KNOWLEDGE-DIFFUSION TOOL ON THE EXAMPLE OF IT SECTOR - Sztangret, Izabela (Acta Scientiarum Polonorum. Oeconomia, 2016)
In connection withthe emergence of the concept of participatory design (also known as co-design) in the 1960s, or later concepts of crowdsourcing and community of practice (that were further consequences of the development of the aforementioned concept) attention must be drawn to the so-called social media applied by innovative companies (for example of the studied IT sector) in their holistic model of marketing knowledge management forcreation, maintenance and activation of processes of knowledge diffusion with broad group of stakeholders in real time. The paper includes an expanded version of the holistic model of marketing knowledge management that was described in previous publications of the author. It emphasised the element of social media as tools of knowledge diffusion in just-in-time system as applied by IT sector leaders both in the subsystem of knowledge diffusion of knowledge among customer and the subsystem of knowledge diffusion among cooperator.